UV-cured acrylate / dynamic borate dual-network pressure-sensitive adhesive and preparation method thereof

By utilizing the interpenetrating structure and reversible boron-nitrogen coordination bonds of UV-cured acrylate/dynamic borate dual-network pressure-sensitive adhesive, the performance balance and weather resistance deficiencies of traditional UV pressure-sensitive adhesives are solved, achieving high adhesion, high stability, and self-healing functions, making it suitable for flexible electronics and wearable devices.

CN120843022AActive Publication Date: 2025-10-28EAST CHINA UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511359069.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-23
Publication Date
2025-10-28
Estimated Expiration
2045-09-23

AI Technical Summary

Technical Problem

Existing UV-curable acrylic pressure-sensitive adhesives suffer from a contradiction between cohesion and adhesion in terms of performance balance, lack of weather resistance, and lack of self-healing function, making it difficult to meet the requirements of high adhesion, high stability, and long-term use.

Method used

The UV-curable acrylate/dynamic borate dual-network pressure-sensitive adhesive utilizes an interpenetrating network structure and reversible boron-nitrogen coordination bonds, combined with UV photoinitiation and thermal curing, to form an acrylate covalent network and a dynamic borate network, achieving high peel strength, high initial tack, and long-lasting tack, while also possessing self-healing capabilities.

Benefits of technology

It achieves the synergistic requirement of high adhesion and high stability, significantly improves the stability of the material in humid and hot environments, and has self-healing capabilities, thus extending the product's service life.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, and discloses a UV-cured acrylate / dynamic borate dual-network pressure-sensitive adhesive and a preparation method thereof, and the pressure-sensitive adhesive comprises the following components by weight: 50-65% of an acrylate mixed monomer; 15-20% of a dynamic boric acid ester crosslinking system; 1.5 to 3% of a UV photoinitiator; 2-8% of a functional auxiliary agent; and 15-20% of a reactive diluent. The preparation method comprises the steps of premixing system preparation, functional system compounding and UV-thermal synergistic curing, an interpenetrating structure of an acrylate covalent network and a dynamic borate network is constructed through UV curing, and the UV rapid curing characteristic and the self-repairing function of dynamic borate are combined; the problems that the cohesive force and the adhesive force of a traditional UV pressure-sensitive adhesive are difficult to balance, the traditional UV pressure-sensitive adhesive lacks a self-repairing function, and the weather resistance is insufficient are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, specifically to a UV-curable acrylate / dynamic borate dual-network pressure-sensitive adhesive and its preparation method. Background Technology

[0002] UV-curable acrylic pressure-sensitive adhesives have been widely used in numerous fields such as electronic packaging, medical dressings, and labeling due to their significant advantages, including fast curing speed, no volatile organic compound emissions, and low energy consumption. Their core principle is the rapid formation of a cross-linked network with adhesive properties through free radical polymerization of acrylate monomers and prepolymers initiated by ultraviolet light. However, existing technologies still face many insurmountable technical bottlenecks.

[0003] In terms of performance balance, there is an inherent contradiction between the cohesive force and adhesive force of traditional UV-cured acrylic pressure-sensitive adhesives: when the cohesive force is enhanced by increasing the crosslinking density to avoid residue when peeling, the peel strength often drops significantly, by more than 40%; while if the crosslinking density is reduced to ensure initial tack and peel performance, the holding power will be insufficient, and the adhesive will be prone to displacement or detachment under continuous load, making it difficult to meet the application requirements of high adhesion and high stability at the same time.

[0004] Meanwhile, existing products have poor weather resistance. In humid and hot environments, the acrylate molecular chains are prone to hydrolysis, resulting in a tack retention rate of less than 50% after 14 days. Long-term ultraviolet irradiation can also cause yellowing of the adhesive layer and a significant decline in mechanical properties.

[0005] In addition, existing UV-cured acrylic pressure-sensitive adhesives generally lack self-healing capabilities. Once microcracks or local damage occur due to external forces during use, they cannot recover on their own. This not only affects the adhesion performance but also shortens the product's lifespan, which greatly limits their application in flexible electronics, wearable devices, and other scenarios that require repeated deformation. Summary of the Invention

[0006] The purpose of this invention is to provide a UV-curable acrylate / dynamic borate dual-network pressure-sensitive adhesive and its preparation method. This aims to overcome the shortcomings of existing UV-curable pressure-sensitive adhesives, such as difficulty in balancing performance, lack of self-healing function, and insufficient weather resistance.

[0007] To achieve the above objectives, the present invention provides a UV-curable acrylate / dynamic borate dual-network pressure-sensitive adhesive, comprising the following components by weight percentage: Acrylic ester mixed monomers: 50~65%; Dynamic borate ester crosslinking system: 15~20%; UV photoinitiator: 1.5~3%; Functional additives: 2~8%; Reactive diluent: 15~20%; The sum of the weight percentages of the above components is 100%.

[0008] Furthermore, the acrylate mixed monomer is composed of soft monomers, hard monomers and hydroxyl-containing functional monomers in a mass ratio of 60~70:25~35:3~8; the soft monomer is butyl acrylate or isooctyl acrylate, the hard monomer is methyl methacrylate or styrene, and the hydroxyl-containing functional monomer is hydroxyethyl acrylate or hydroxypropyl acrylate.

[0009] Furthermore, the dynamic borate ester crosslinking system is composed of a phenylboronic acid derivative and an amino polyol, with a molar ratio of 1:1.1~1.3; the phenylboronic acid derivative is 3-acrylamidophenylboronic acid or 4-vinylphenylboronic acid, and the amino polyol is diethanolamine or polyethylene glycol diamine.

[0010] Furthermore, the UV photoinitiator is composed of a small molecule photoinitiator and a free radical scavenger in a mass ratio of 1:3 to 5; the small molecule photoinitiator is 1-hydroxycyclohexylphenyl ketone, and the free radical scavenger is 2,2,6,6-tetramethylpiperidine nitroxide free radical.

[0011] Furthermore, the functional additives include a nano-reinforcing phase and a tackifying resin. The nano-reinforcing phase is acrylate-modified nano-montmorillonite with a particle size of 50-100 nm, and the tackifying resin is hydrogenated rosin glycerol ester.

[0012] Furthermore, the active diluent is trimethylolpropane triacrylate or ethoxylated trimethylolpropane triacrylate.

[0013] On the other hand, the present invention also provides a method for preparing a UV-curable acrylate / dynamic borate dual-network pressure-sensitive adhesive, comprising the following steps: S1. Preparation of premixed system: Add acrylate mixed monomers and reactive diluent to the reactor, stir for 10-15 min under nitrogen protection, add dynamic borate ester crosslinking system, and stir at 40-50℃ for 30-40 min until completely dissolved; S2, Functional System Composite: Add UV photoinitiator and functional additives to the premixed system obtained in S1, stir for 60-90 minutes under light-protected conditions to form a uniform solution, and control the solid content to 70-80%; S3, UV-thermal synergistic curing: The adhesive is uniformly applied to the surface of the substrate, first irradiated with 365nm UV light, and then thermally cured at 50~70℃ for 20~40min to obtain a dual-network pressure-sensitive adhesive.

[0014] Furthermore, in S3, the coating speed is 30~50 m / min, the coating thickness is 80~120 μm, and the light irradiation intensity is 80~120 mW / cm². 2 The exposure time is 150~200mJ / cm. 2 .

[0015] The advantages and positive effects of this invention are: (1) Excellent performance balance: The interpenetrating structure of the acrylate covalent network and the dynamic borate ester network successfully solves the problem of the contradiction between cohesion and adhesion in traditional UV pressure-sensitive adhesives. The acrylate network provides basic cohesion to ensure tack, while the dynamic borate ester network achieves interface self-adaptation through the reversibility of boron-nitrogen coordination bonds, so that the adhesive layer has high peel strength, high initial tack and long-term tack, meeting the synergistic requirements of high adhesion and high stability.

[0016] (2) It has self-healing function: The presence of reversible boron-nitrogen coordination bonds in the dynamic borate ester network enables the adhesive layer to quickly repair scratches, solving the defect that traditional UV pressure-sensitive adhesives cannot recover after damage, significantly extending the product's service life, and is especially suitable for scenarios such as flexible electronics and wearable devices that require repeated deformation.

[0017] (3) Significantly improved weather resistance: The hydrolysis resistance of dynamic borate ester bonds and the barrier function of nano-reinforced phase greatly improve the stability of the material in humid and hot environments.

[0018] The technical solution of the present invention will be further described in detail below through embodiments. Detailed Implementation

[0019] The technical solution of the present invention will be further described below through embodiments.

[0020] Unless otherwise defined, the technical or scientific terms used in this invention shall have the ordinary meaning as understood by one of ordinary skill in the art to which this invention pertains.

[0021] Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without inventive effort are within the scope of protection of this invention. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to national standards. Experimental instruments, equipment, and reagents in the following embodiments that do not specify their sources are all commercially available materials.

[0022] Unless otherwise defined or stated, all technical and scientific terms used in this invention have the same meaning as those skilled in the art. Furthermore, any methods and materials similar to or equivalent to those described herein can be applied to the methods of this invention. It should be noted that, unless otherwise specified, the embodiments and features described in this invention can be combined with each other.

[0023] The method for preparing acrylate-modified nano-montmorillonite used in this invention includes the following steps: Pretreatment: The nano-montmorillonite was vacuum dried at 100°C for 5 hours to remove adsorbed water.

[0024] Dispersion: The dried nano-montmorillonite was dispersed in anhydrous ethanol at a mass ratio of 1:20, and then ultrasonically dispersed in an ultrasonic cell disruptor at a power of 1000W for 40 minutes to obtain a uniform suspension.

[0025] Modification reaction: 4% (by mass of montmorillonite) of silane coupling agent KH-570 (γ-(methacryloyloxy)propyltrimethoxysilane) was added to the above suspension, and the pH of the system was adjusted to 5 with acetic acid. The mixture was transferred to a three-necked flask equipped with a condenser and mechanically stirred at 400 rpm for 7 hours at 80°C under nitrogen protection. The modification principle is that the methoxysilane in the KH-570 molecule undergoes a condensation reaction with the silanol groups on the surface of montmorillonite after hydrolysis, thereby grafting the terminal methacryloyloxy group onto the surface of montmorillonite.

[0026] Washing and drying: After the reaction, the modified product was obtained by centrifugation and washed three times with anhydrous ethanol and deionized water to remove unreacted coupling agent and byproducts. Finally, the product was dried to constant weight in a vacuum oven at 80℃, ground, and passed through a 400-mesh sieve to obtain acrylate-modified nano-montmorillonite.

[0027] Example 1 First, weigh out the mixed monomers of acrylates (40% butyl acrylate, 15% methyl methacrylate, and 3% hydroxyethyl acrylate) and 16% of the reactive diluent trimethylolpropane triacrylate according to the weight percentage. Add them to a 500mL four-necked reactor, purge with nitrogen at a flow rate of 0.5L / min, and stir at 300rpm for 12 minutes. Then add the dynamic borate ester crosslinking system (7% 3-acrylamidophenylboronic acid and 11% diethanolamine), heat to 45℃, adjust the stirring speed to 500rpm and continue stirring for 35 minutes until the system is completely dissolved and forms a homogeneous transparent liquid.

[0028] Next, under light-protected conditions, a UV photoinitiator (2% 1-hydroxycyclohexylphenyl ketone, 0.5% 2,2,6,6-tetramethylpiperidine nitroxide radical) and functional additives (2.5% acrylate-modified nano-montmorillonite, 3% hydrogenated rosin glycerol ester) were added to the above system. The mixture was stirred at 600 rpm for 75 minutes, and the solid content was adjusted to 75% ± 1% by rotary evaporation to obtain a light yellow adhesive.

[0029] Finally, a microgravure coater was used to uniformly coat the adhesive onto a 50μm thick PET substrate at a coating speed of 40m / min, controlling the wet film thickness to be 100μm±5μm. The substrate was then immediately cured by 365nm UV light at an intensity of 100mW / cm². 2 The exposure was 180 mJ / cm. 2The sample was then transferred to a 60℃ / 40% RH constant temperature and humidity chamber for heat curing for 30 minutes, and then allowed to cool naturally to room temperature to obtain a pressure-sensitive adhesive sample with a dry film thickness of 65μm±3μm.

[0030] Example 2 Weigh out the mixed monomers of acrylate (40% isooctyl acrylate, 17% styrene, 3% hydroxypropyl acrylate) and 15% ethoxylated trimethylolpropane triacrylate as reactive diluent by weight percentage, add them to the reactor, and stir at 300 rpm for 15 minutes under nitrogen protection; add the dynamic borate ester crosslinking system (6% 4-vinylphenylboronic acid, 11% polyethylene glycol diamine), heat to 40°C, and stir at 500 rpm for 38 minutes until completely dissolved.

[0031] Under light-protected conditions, add UV photoinitiator (1.6% 1-hydroxycyclohexylphenyl ketone, 0.4% 2,2,6,6-tetramethylpiperidine nitroxide radical) and functional additives (3% acrylate-modified nano-montmorillonite, 3% hydrogenated rosin glycerol ester), stir at 600 rpm for 80 minutes, and adjust the solid content to 72% ± 1%.

[0032] The adhesive was uniformly coated onto the PET substrate using a microgravure coating machine at a speed of 35 m / min, resulting in a wet film thickness of 90 μm ± 5 μm. The film was then immediately cured by irradiation with 365 nm UV light at an intensity of 90 mW / cm². 2 The exposure amount was 160 mJ / cm. 2 The sample was obtained by heat curing at 55℃ / 45%RH for 35 minutes and then cooling.

[0033] Example 3 The acrylate monomer mixture (42% butyl acrylate, 20% methyl methacrylate, and 3% hydroxyethyl acrylate) and 15% reactive diluent trimethylolpropane triacrylate were added to the reactor and stirred at 300 rpm for 12 minutes under nitrogen protection. The dynamic borate ester crosslinking system (6% 3-acrylamidophenylboronic acid and 9% diethanolamine) was added and stirred at 500 rpm for 35 minutes at 45°C until dissolved.

[0034] Under light-protected conditions, add UV photoinitiator (1.2% 1-hydroxycyclohexylphenyl ketone, 0.3% 2,2,6,6-tetramethylpiperidine nitroxide radical) and functional additives (1.5% acrylate-modified nano-montmorillonite, 2% hydrogenated rosin glycerol ester), stir at 600 rpm for 75 minutes, and adjust the solid content to 75% ± 1%.

[0035] The adhesive was uniformly coated onto the PET substrate using a microgravure coating machine at a speed of 40 m / min, resulting in a wet film thickness of 100 μm ± 5 μm. The film was then immediately cured by irradiation with 365 nm UV light at an intensity of 100 mW / cm². 2The exposure was 180 mJ / cm. 2 The sample was obtained by heat curing at 70℃ / 35%RH for 25 minutes and then cooling.

[0036] Example 4 Weigh out the mixed monomers of acrylates (35% isooctyl acrylate, 12% styrene, 3% hydroxypropyl acrylate) and 20% of the reactive diluent ethoxylated trimethylolpropane triacrylate, add them to the reactor and stir at 300 rpm for 12 minutes under nitrogen protection; add the dynamic borate ester crosslinking system (8% 4-vinylphenylboronic acid, 12% polyethylene glycol diamine), and stir at 500 rpm for 35 minutes at 45°C until dissolved.

[0037] Add UV photoinitiator (2.4% 1-hydroxycyclohexylphenyl ketone, 0.6% 2,2,6,6-tetramethylpiperidine nitroxide radical) and functional additives (3% acrylate-modified nano-montmorillonite, 4% hydrogenated rosin glycerol ester) to the mixture in the dark. Stir at 600 rpm for 75 minutes and adjust the solid content to 75% ± 1%.

[0038] The adhesive was uniformly coated onto the PET substrate using a microgravure coating machine at a speed of 40 m / min, resulting in a wet film thickness of 100 μm ± 5 μm. The film was then immediately cured by irradiation with 365 nm UV light at an intensity of 100 mW / cm². 2 The exposure level is 200 mJ / cm. 2 The sample was obtained by heat curing at 65℃ / 40%RH for 30 minutes and then cooling.

[0039] Comparative Example 1 The dynamic borate ester crosslinking system in Example 1, namely 7% 3-acrylamidophenylboronic acid + 11% diethanolamine, was replaced with an equal proportion of 18% pentaerythritol triacrylate. The remaining raw material composition and preparation process parameters were the same as in Example 1.

[0040] Comparative Example 2 The formulation composition is the same as in Example 1, and the premixing and compounding steps in the preparation process are the same as in Example 1; after coating, it is only exposed to 365nm UV light (intensity 100mW / cm). 2 Exposure amount 180mJ / cm 2 The sample was cured by irradiation, skipping the 60℃ / 40% RH heat curing step, and was directly cooled to obtain the sample.

[0041] Comparative Example 3 The only difference was that 2.5% of the acrylate-modified nano-montmorillonite in the functional additives was replaced with an equal proportion of 2.5% of micron-sized unmodified montmorillonite (particle size 1-5 μm); the remaining components and preparation steps were the same as in Example 1.

[0042] Comparative Example 4 The 0.5% 2,2,6,6-tetramethylpiperidine nitroxide radical in the UV photoinitiator was replaced with an equal proportion of 0.5% UV-944, and the remaining components and preparation steps were the same as in Example 1.

[0043] Performance testing: (1) Adhesion properties: 180° peel strength: The peel force of the pressure-sensitive adhesives prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were tested according to the method specified in GB / T 2792-2014.

[0044] Initial tack: The initial tack of the pressure-sensitive adhesives prepared in Examples 1-4 and Comparative Examples 1-4 were tested according to GB / T 31125-2014, using the ring tack method.

[0045] Adhesion holding: According to GB / T 4851-2014, a 1kg weight is suspended at 40℃, and the time of detachment is recorded.

[0046] (2) Functions and mechanical properties: Self-healing performance: Scratches with a depth of 20%~30% of the thickness were made on the surface of a 40mm×5mm×0.5mm sample, and the time for the scratches to be completely healed was recorded when the sample was placed in an environment of 100℃.

[0047] Tensile strength and elongation at break: tested using a universal testing machine according to the method specified in GB / T 1040-2006.

[0048] (3) Moisture and heat resistance test: The protective film is attached to the glass plate and placed in a constant temperature and humidity chamber at 80℃ and 90%RH for 100h. After taking it out, it is naturally cooled to room temperature. After peeling, observe whether there is any residual adhesive on the surface.

[0049] The performance test results of the pressure-sensitive adhesives prepared in Examples 1-4 and Comparative Examples 1-4 are shown in Table 1: Table 1. Performance test results of the pressure-sensitive adhesives prepared in Examples 1-4 and Comparative Examples 1-4.

[0050] ; As shown in Table 1, in terms of adhesion performance, the peel force (10.2~10.8 N / 25 mm), initial tack (32~38 N / cm), and holding power (>72 h) of Examples 1~4 are significantly better than those of the comparative examples, with Example 1 showing the best performance. This is due to the synergistic effect of the dual networks: in the acrylate network, the compliant segments of the soft monomers ensure good wetting of the adhesive layer and the substrate, the covalent crosslinking formed by the hard monomers and the hydroxyl-containing monomers provides sufficient cohesive force, and the dynamic borate ester network achieves interface self-adaptation through the reversibility of boron-nitrogen coordination bonds. This avoids the contradiction of high cohesion and low adhesion inherent in traditional covalent networks, and also improves the balance between peel force and holding power through segment recombination.

[0051] In terms of mechanical properties, the tensile strength (28.6~33.5 MPa) and elongation at break (640%~720%) of Examples 1~4 are much higher than those of the comparative examples, with Example 1 exhibiting the highest tensile strength (33.5 MPa). This is attributed to the rigid skeleton-flexible buffer mechanism of the dual-network structure: the acrylate covalent network forms a three-dimensional cross-linked structure through UV curing, providing basic strength, and the optimization of the hard monomer ratio further enhances tensile strength; the dynamic borate ester network absorbs impact energy and disperses stress through the reversible breaking and recombination of bonds, thus preventing brittle fracture.

[0052] Regarding self-healing performance, the self-healing time of Examples 1-4 was 1.5 hours, which is far superior to the comparative examples (4 to >24 hours), demonstrating highly efficient self-healing capabilities. The core reason is the reversibility of boron-nitrogen coordination bonds in the dynamic borate ester system. At high temperatures, the dynamic bonds at the scratch can break and recombine rapidly, driving the interface to restore its integrity through intermolecular forces.

[0053] In the damp heat resistance test, Examples 1-4 showed no residue after being placed at 80℃ / 90% RH for 100 hours, while Comparative Example 1 showed obvious residue. This is because the layered structure of the acrylate-modified nano-montmorillonite blocks water vapor penetration and delays the hydrolysis of acrylate segments. At the same time, the dynamic borate ester bond has better water resistance than the traditional ester bond and is not easily broken in a damp heat environment, thus avoiding residue degradation of the adhesive layer.

[0054] Therefore, this invention discloses a UV-curable acrylate / dynamic borate dual-network pressure-sensitive adhesive. It constructs an interpenetrating structure of an acrylate covalent network and a dynamic borate network through UV curing. The acrylate network is formed by UV-initiated polymerization, while the dynamic borate network achieves reversible cross-linking through boron-nitrogen coordination. This invention innovatively combines the rapid curing characteristics of UV with the self-healing function of dynamic borate, solving problems such as the difficulty in balancing cohesion and adhesion, lack of self-healing function, and insufficient weather resistance in traditional UV pressure-sensitive adhesives.

[0055] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. A UV-curable acrylate / dynamic borate dual-network pressure-sensitive adhesive, characterized in that, By weight percentage, it includes the following components: Acrylic ester mixed monomers: 50~65%; Dynamic borate ester crosslinking system: 15~20%; UV Photoinitiator: 1.5~3%; Functional additives: 2~8%; Reactive diluent: 15~20%; The sum of the weight percentages of all the above components is 100%; The dynamic borate ester crosslinking system is composed of a phenylboronic acid derivative and an amino polyol in a molar ratio of 1:1.1~1.3; the phenylboronic acid derivative is 3-acrylamidophenylboronic acid or 4-vinylphenylboronic acid, and the amino polyol is diethanolamine or polyethylene glycol diamine; The UV photoinitiator is composed of a small molecule photoinitiator and a free radical scavenger in a mass ratio of 1:3 to 5; the small molecule photoinitiator is 1-hydroxycyclohexylphenyl ketone, and the free radical scavenger is 2,2,6,6-tetramethylpiperidine nitroxide free radical. The functional additives include a nano-reinforcing phase and a tackifying resin. The nano-reinforcing phase is acrylate-modified nano-montmorillonite with a particle size of 50-100 nm, and the tackifying resin is hydrogenated rosin glycerol ester.

2. The dual-network pressure-sensitive adhesive according to claim 1, characterized in that, The acrylate mixed monomers are composed of soft monomers, hard monomers and hydroxyl-containing functional monomers, with a mass ratio of 60~70:25~35:3~8; the soft monomers are butyl acrylate or isooctyl acrylate, the hard monomers are methyl methacrylate or styrene, and the hydroxyl-containing functional monomers are hydroxyethyl acrylate or hydroxypropyl acrylate.

3. The dual-network pressure-sensitive adhesive according to claim 1, characterized in that, The active diluent is trimethylolpropane triacrylate or ethoxylated trimethylolpropane triacrylate.

4. The preparation method of the UV-curable acrylate / dynamic borate dual-network pressure-sensitive adhesive according to any one of claims 1-3, characterized in that, Includes the following steps: S1. Preparation of premixed system: Add acrylate mixed monomers and reactive diluent to the reactor, stir for 10-15 min under nitrogen protection, add dynamic borate ester crosslinking system, and stir at 40-50℃ for 30-40 min until completely dissolved; S2, Functional System Composite: Add UV photoinitiator and functional additives to the premixed system obtained in S1, stir for 60-90 minutes under light-protected conditions to form a uniform solution, and control the solid content to 70-80%; S3, UV-thermal synergistic curing: The adhesive is uniformly applied to the surface of the substrate, first irradiated with 365nm UV light, and then thermally cured at 50~70℃ for 20~40min to obtain a dual-network pressure-sensitive adhesive.

5. The preparation method according to claim 4, characterized in that, In S3, the coating speed is 30~50 m / min, the coating thickness is 80~120 μm, and the light irradiation intensity is 80~120 mW / cm². 2 The exposure time is 150~200mJ / cm. 2 .

Citation Information

Patent Citations

  • Two-photon polymerization 3D printing photoresist based on dynamic borate bond as well as preparation method and application of two-photon polymerization 3D printing photoresist

    CN119505087A

  • Degradable mobile phone gum material and preparation process thereof

    CN120082305A

  • Optical cement with dynamic bond exchange and gradient curing functions and preparation method thereof

    CN120648401A

  • Boronate adhesives for apparel products

    US11712873B1